An approach to the EUDR regulation (2023) with a particular focus on due diligence (Revista Española de Estudios Agrosociales y Pesqueros, 2025)
The EUDR Regulation, adopted in 2023, reinforces the EU's climate commitment within the European Green Deal, evolving the FLEGT and EUTR regulations. It establishes an obligation of result: to ensure that certain products do not come from deforested or degraded lands. It covers raw materials such as soy, cocoa, coffee, beef, timber, rubber and palm oil, affecting operators and traders in the EU. They can only be placed on the market if they meet three requirements: they are not linked to deforestation, they have been produced in accordance with the legislation of the country of origin (environmental, labour, tax, human rights, etc.) and they are supported by a due diligence declaration. This article systematically analyzes the new cross-compliance established by the EUDR with the technological requirements they imply and its impact on the sustainable forest management of our forests.
Keywords: Sustainable forest manegement; rural development; Deforestation; Conditionality; Risk; Information; Blockchain